If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x(0) + 3y = 6 Reorder the terms for easier multiplication: -1 * 0x + 3y = 6 Multiply -1 * 0 0x + 3y = 6 Anything times zero is zero. 0x + 3y = 6 Remove the zero: 3y = 6 Solving 3y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '3'. y = 2 Simplifying y = 2
| ln(5x-1)=ln(2x+8) | | -2.4x-10.25=1.75 | | 5x^2+14x-2=0 | | -x+3(0)=6 | | a*x^2-(a-b)*x=0 | | r=x^4cos(x) | | 1000/400 | | 5X-20=21-7X | | -5x+7=0+2x | | 5(m-2)=30 | | (4-i)/(6-2i) | | 1000/400x | | 9(d-5)=90 | | (0)=-2x+1 | | y=-2(0)-8 | | y=-2x^2-12x+22 | | 7x-15=10x+8 | | 10x+1=15-5x | | 16(p+2)=32 | | 2x^2-12-1=0 | | 9x-2y=40 | | 4x+1+3x=-83 | | 3.6x-2.25=15.75 | | 30/5=5x | | 8(0)-6y=48 | | 5x+12y=148 | | 80x^5=20x^2 | | 80x^5=20x^3 | | 8x-6(0)=48 | | 3lnx^2-lnx=0 | | 4x-3(2-3x)=20 | | 16t=156 |